2016
DOI: 10.1007/s10639-016-9557-y
|View full text |Cite
|
Sign up to set email alerts
|

School children’s use of digital devices, social media and parental knowledge and involvement – the case of Abu Dhabi

Abstract: This paper looks at the usage of social media devices and applications, and parental knowledge and involvement among Abu Dhabi children in Grade 6 or higher. It examines the young children's usage of personal computers, mobile phones and tablet PCs, and social media related apps. The paper tries to understand the reasons for joining or not joining online social networking. It explores the parental knowledge of such activities and their chance of being invited to join their children's' social networking groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…These characteristics meant that the data in our study were gathered from younger children and a larger sample population than the previous study from India. [ 6 ] The average screen time per day was found to be 7.02 h (range: 1–12 h) in our study, which is higher than that found by Mohan et al ,[ 6 ] who reported an average screen time of 3.9 h. This figure was also higher than those reported by UK studies, which found that participants spent approximately 4 h using display devices, and by Badri et al ,[ 10 ] who reported that students spent an average of 5.2 h per day on social media. These two reports were published before online learning was made mandatory during the COVID-19 pandemic, which may be why they report students spending less time using display devices.…”
Section: Discussioncontrasting
confidence: 74%
“…These characteristics meant that the data in our study were gathered from younger children and a larger sample population than the previous study from India. [ 6 ] The average screen time per day was found to be 7.02 h (range: 1–12 h) in our study, which is higher than that found by Mohan et al ,[ 6 ] who reported an average screen time of 3.9 h. This figure was also higher than those reported by UK studies, which found that participants spent approximately 4 h using display devices, and by Badri et al ,[ 10 ] who reported that students spent an average of 5.2 h per day on social media. These two reports were published before online learning was made mandatory during the COVID-19 pandemic, which may be why they report students spending less time using display devices.…”
Section: Discussioncontrasting
confidence: 74%
“…In a study conducted in India before the COVID era, only 40% of children used smartphones for the purpose of a school project, and only 3.3% used> 5 h per day on digital devices [7]. In addition, 73.50% of children used digital devices at a distance of <18 inches, in contrast to a study by Ichapujani et al [8] in which 56% maintained a reasonable range of digital devices of students were associated with weight in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Among the social media used by Emirati students, WhatsApp had the largest user base at 86.5%, followed by Kik Messenger (36.3%), Facebook Messenger (32.3%), Viber (26.9%), and MS Messenger (26.5%) (Badri et al, 2017b). These figures reflected approximately 82% of the participants, who had accounts in various sites.…”
Section: United Arab Emirates and Technology In Educationmentioning
confidence: 99%